Key Variables on Property Marketing in Bali: Application of Micmac Method - Putra, Gde Bagus Brahma; Sudharma, I Wayan Priyana Agus; Rahmadani, Dian Ayu (Asia Pacific Journal of Management and Education (APJME), 2020)
Bali as a tourism area has its own charm and positive economic potential for the property business. Organizational and management aspects are needed to determine business strategies. This certainly affects the decision for investors in investing in the property sector that is most popular. This study seeks to analyze the key variables that affect the development of the property business in Bali in the long run. MICMAC (Matrix of Cross Impact Multiplications Applied to a Classification) is used to identify variables that influence the sustainability of property marketing in Bali.